Real time analysis of the nystagmus and movement patterns in balance disturbances - Lanzarini, Laura Cristina (1996)
Balance disorders are difficult to manage in a diagnosis and/or trealment situation. This article presents an application for the diagnosis of balance disorders in real time, and it has been jointly developed by the UDI and the Medical Sciences Faculty from La Plata University, and is currently in use at consulting rooms. At present we have already examined more than 300 patients, under these systems and controlled them after the necessary treatment. Patient response processing is emphasized by using signal pressing techniques and image treatment in real time, the aim being the obtention of a totally automatic diagnosis.